Effects of age, gender, and socio-economic status on the incidence of spinal cord injury: an assessment using the eleven-year comprehensive nationwide database of Taiwan - Wu, Jau-Ching; Chen, Yu-Chun (Journal of neurotrauma, 2012)
This study used an 11-year nationwide database to analyze the incidence of spinal cord injury (SCI) in subgroups by age, gender, injury level, etiology, and socioeconomic status. The National Health Insurance Research Database of Taiwan, covering over 99% of the population accumulated from 1998 to 2008, was analyzed. All SCI patients>20 years of age and admitted to medical services were identified. Of the 168,832,051.4 person-years, 41,586 newly established diagnoses of SCI were identified, for a SCI incidence of 2.46 per 10,000 person-years, and 61.2% were traumatic. Cervical SCI was the highest at 1.28, followed by lumbar 0.56, and thoracic 0.30 per 10,000 person-years. Males were more likely to have SCI (HR=1.52). Compared to the age group of 20-39 years, the 40-59-year-old group and the group aged≥60 years were more likely to have SCI (HR=1.66 and 2.12, respectively). Those with the lowest insurance premium (which represents income level) were more likely to have SCI compared to the highest insurance premium group (HR=1.86). Those living in the eastern area were more likely to have SCI than those living in the northern area (where political and economic centers are located) (HR=1.52). Those in the most rural area were more likely (HR=1.69) to have SCI than those in the most urbanized areas. The overall national incidence of adult SCI in Taiwan was 246 per million-person-year. Several groups, such as elderly men with lower socioeconomic status, were more likely to experience SCI.
Online ahead of print:July 27, 2011
Gesehen am 15.10.2018